The effect of hexagonal nano boron nitride on mechanical performances and machinability behaviors of basalt fabric reinforced epoxy composites. (December 2021) - Gumus, Fatma B; Ceritbinmez, Ferhat; Yapici, Ahmet
The aim of this work is to investigate the effect of the hexagonal nano boron nitride (h-BN) doped epoxy on the mechanical performances and machinability behaviors of basalt fiber (BF) composites. The h-BN has used as a dopant with a weight rate of 1 wt. %. The polymer composites were prepared by the vacuum bagging method and specimens were processed with abrasive water jet machining (AWJM) to analyze the machinability of the material. A circular hole with an 8 mm size was machined by abrasive water jet (AWJ) on the composite plate with a thickness of 2.3 ± 0.1 mm using the garnet size of 80 µm as an abrasive. Taper angle and circularity of machined hole, the entry-exit hole diameter, delamination, splintering, burring, thickness, and hardness were measured. Results indicate that cutting speed has a high influence on the taper angle and circularity respectively.